The influence of education level and motivation on the performance of employees in the secretariat of the regional people's representative council (DPRD) of Tangerang city - Saeful Bahri; Herayati Herayati; Martinus Wahyu Purnomo (International Journal of Applied Finance and Business Studies, 2023)
Based on the researcher's observations, it is emphasized that there is a relationship between the level of education and motivation of employees with their performance in the Secretariat of the Regional People's Representative Council (DPRD) of Tangerang City. The issue to be examined is to what extent the level of education and motivation of employees can impact the effectiveness and productivity of work in that environment. The purpose of this study is to determine whether there is a combined influence of the level of education and motivation on the performance of employees in the Secretariat of the DPRD of Tangerang City. The method used is quantitative statistics with three variables: level of education (X1), motivation (X2), and employee performance (X3), with a sample of 39 respondents, namely employees of the Secretariat of the DPRD of Tangerang City. The results of this study are obtained through t-tests, which indicate that there is a significant partial influence of variable X1 on Y, as X1 has a value of 0.000 < 0.05. However, for variable X2, there is no significant partial influence on Y, as X2 has a value of 0.499 > 0.05. The results of the F-test in this study, which examines the variables together (simultaneously), show that the level of education and motivation have a positive and significant influence on employee performance, as the significance value is smaller than 0.05. Therefore, the null hypothesis (Ho) in this study is rejected, and the alternative hypothesis (Ha) is accepted.